Initial Growth and Survival of Different Forest Tree Species in Assam - Ahmed, A. A.; Puzari, N. N. (Indian Forester, 1991)
Over the four years compared, Azadirachta indica consistently had the highest average plant height (6.21 m) and girth (47 cm) in field experiment with indigenous and exotic forest tree species. Trewia nudiflora had the lowest plant height while Albizia lucida had the lowest girth. Among all the species, Azadirachta indica recorded the lowest moisture content and highest dry matter accumulation of wood.